2006
DOI: 10.1158/0008-5472.can-05-2112
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Oncoprotein Prothymosin α Triggers a p53 Response that Involves p53 Acetylation

Abstract: Activation of the tumor suppressor protein p53 is a critical cellular response to various stress stimuli and to inappropriate activity of growth-promoting proteins, such as Myc, Ras, E2F, and B-catenin. Protein stability and transcriptional activity of p53 are modulated by protein-protein interactions and post-translational modifications, including acetylation. Here, we show that inappropriate activity of prothymosin A (PTMA), an oncoprotein overexpressed in human cancers, triggers a p53 response. Overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 55 publications
2
26
0
1
Order By: Relevance
“…Increased intracellular expression of ProTa, which has been thought to be an oncoprotein (Karapetian et al 2005;Kobayashi et al 2006), has been observed in several types of human cancer. Recently, several groups have applied IHC techniques and reported that ProTa is overexpressed in various cancers, e.g., gastric (Leys et al 2007), prostate (Suzuki et al 2006), and thyroid (Letsas et al 2005) cancer, and might therefore be considered as an intracellular tumor biomarker.…”
mentioning
confidence: 99%
“…Increased intracellular expression of ProTa, which has been thought to be an oncoprotein (Karapetian et al 2005;Kobayashi et al 2006), has been observed in several types of human cancer. Recently, several groups have applied IHC techniques and reported that ProTa is overexpressed in various cancers, e.g., gastric (Leys et al 2007), prostate (Suzuki et al 2006), and thyroid (Letsas et al 2005) cancer, and might therefore be considered as an intracellular tumor biomarker.…”
mentioning
confidence: 99%
“…ProTa is a proliferation-related protein localizing in the nucleus where it is engaged in activity regulation of several stress-related transcription factors, such as p53 tumour suppressor and Nrf2 (Karapetian et al, 2005;Kobayashi et al, 2006;Zakharova et al, 2008). Caspase-3-mediated cleavage detaches a short C-terminal peptide of ProTa.…”
Section: Identification Of the Phytaspasementioning
confidence: 99%
“…It has been demonstrated that overexpression of Ptmaa causes apoptosis in cultured cells (Kobayashi et al 2006). However, Ptma may function as an apoptosis inhibitor in some physiological conditions, such as under stress, stroke or ischemia (Letsas and Frangou-Lazaridis 2006;Fujita et al 2009).…”
Section: Overexpression Of Ptmaa Protects Zebrafish Larvae From Uvb-mmentioning
confidence: 99%
“…Knockdown of Ptma synthesis by antisense oligonucleotides and RNAi leads to cell division arrest and inhibits prostate tumor cell growth and invasion in vitro (Sburlati et al 1991;Suzuki et al 2006). Ptma also plays a role in the mitochondria or p53 pathways to regulate apoptosis (Markova et al 2003;Kobayashi et al 2006). In addition, Ptma could be used as a potential tumor marker for early detection, estimation of tumor aggressiveness, and treatment response in certain types of human cancers, such as breast (Magdalena et al 2000), lung (Sasaki et al 2001a), prostate (Suzuki et al 2006), bladder (Tzai et al 2006), gastric (Leys et al 2007) and rectal cancer (Ojima et al 2007).…”
Section: Introductionmentioning
confidence: 99%